Short-Term Rental Property Market in Federal Capital Territory Abuja, Nigeria: An Assessment of Guest Satisfaction with Interior Decoration - Ayuba, B.; Sani, A.; Asinya, M. E.; Usman, M. K. (International Journal of Real Estate, 2025)
Abuja's dynamic real estate milieu has witnessed a palpable surge in short-term rental properties, underscoring the burgeoning market potential. However, even in this expanding field, there is a noticeable lack of academic research on the effects of interior design on the functionality and marketability of short-term rental houses. Therefore, this paper uses appropriate standard procedures to assess Guest Satisfaction with Interior Decoration in Short Term Rental Property Market in the Federal Capital Territory Abuja Nigeria with a view to understand how does how interior decoration influence the satisfaction overall contentment with the stay after collecting data from 258 respondents through a structured questionnaire administration. The data collected was analyzed using SPSS Software and the results were presented in charts and graphs. The findings indicated that; guests are actively seeking properties with visually appealing and well-designed interior spaces, emphasizing the critical role of interior decoration in attracting guests and influencing their booking decisions; the guests' satisfaction can be attributed to the attractiveness and quality of the interior decorating, highlighting the role that it plays in improving the whole guest experience and creating pleasant recollections of the stay; guests who are satisfied with the interior decoration are more inclined to return for future stays, indicating the important role of interior design in fostering guest loyalty and retention; property owners frequently struggle to allocate enough funds to attain the ideal interior design results, which could jeopardize the standard and attraction of their lodgings; property owners can make use of Abuja's rich cultural legacy by using locally produced materials and hiring local craftspeople, which would help to create a sense of genuineness and connection with visitors.   Therefore, the study concluded that interior decoration enhances guest satisfaction in short-term rental properties in the study area. The study further recommends that to attract the rich short-term rental market, property owners in luxurious areas like Maitama should emphasise elegance and contemporary aesthetics in their interiors.
Keywords: Short-term rental property; Guest satisfaction; Interior decoration